The ball-room monitor, or, Guide to the learner; containing the most complete sets of quadrilles ever published. - Brooks, C. (Professor) (Philadelphia, J. H. Johnson, 1866)
Like many other nineteenth-century dance manuals, much of the material in The Ball-room monitor is not original but is borrowed from previously published sources. The manual, which would fit into a pocket, contains information on quadrilles (called cotillions by Brooks), waltz, polka redowa, and schottisch. Additionally, the manual contains numerous variety quadrilles--polka quadrilles, schottisch quadrilles, Polaca quadrilles, Varsoviana quadrilles, and a mazurka quadrille.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; Quadrille (Dance) -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals